Utilizing Adaptive Droop Control to Improve the Accuracy of Load Power Balancing in DC Nanogrid Batteries - Paisey, Fourys Yudo Setiawan; Soeprijanto, Adi; Pamuji, Feby Agung (Engineering, Technology & Applied Science Research, 2025)
This paper proposes an independent and flexible control strategy for Battery Energy Units (BEUs) in autonomous DC Nano Grids (DCNGs) using a communication-based system. The proposed strategy employs a hierarchical control approach, where the primary control manages power balance among BEUs, while the secondary control mitigates DC bus voltage deviations caused by droop operation. This ensures optimal power distribution while considering line resistance variations, State of Charge (SoC), and virtual power levels. The method prioritizes BEUs with higher SoC to contribute more power to the load while reducing the burden on lower SoC units. Additionally, a voltage recovery technique is implemented to maintain DC grid voltage stability. Beyond technical improvements, these findings can contribute to more efficient energy management in decentralized renewable energy systems, supporting the scalability of sustainable nanogrid infrastructures in remote or off-grid communities. An additional advantage is that in the event of a failure in the control of BEU1, the control of the unaffected BEU remains operational, ensuring system continuity. A comprehensive simulation comparison between conventional and the proposed method was conducted in MATLAB/Simulink under varying load power conditions. The results demonstrate that the proposed control strategy significantly improves power balancing accuracy and voltage stability.